Reaching for the Sun : How Plants Work / [electronic resource] - King, John (Cambridge : Cambridge University Press, 2011)
From their ability to use energy from sunlight to make their own food, to combating attacks from diseases and predators, plants have evolved an amazing range of life-sustaining strategies. Written with the non-specialist in mind, John King's lively natural history explains how plants function, from how they gain energy and nutrition to how they grow, develop and ultimately die. New to this edition is a section devoted to plants and the environment, exploring how problems created by human activities, such as global warming, pollution of land, water and air, and increasing ocean acidity, are impacting on the lives of plants. King's narrative provides a simple, highly readable introduction, with boxes in each chapter offering additional or more advanced material for readers seeking more detail. He concludes that despite the challenges posed by growing environmental perils, plants will continue to dominate our planet.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Plants; Botany